ISNAR The International Service for National Agricultural Research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
International Service for National Agricultural ResearchFood requirements in many developing countries keep in creasing at unprecedented rates. Consumption patterns change with rapid urbanization and increasing incomes. Agricultural practices, in...